Applications of Telemedicine and Telecommunications to Disaster Medicine: Historical and Future Perspectives - Garshnek, Victoria (American Medical Informatics Association, 1999)
Disaster management utilizes diverse technologies to accomplish a complex set of tasks. Despite a decade of experience, few published reports have reviewed application of telemedicine (clinical care at a distance enabled by telecommunication) in disaster situations. Appropriate new telemedicine applications can improve future disaster medicine outcomes, based on lessons learned from a decade of civilian and military disaster (wide-area) telemedicine deployments. This manuscript reviews the history of telemedicine activities in actual disasters and similar scenarios as well as ongoing telemedicine innovations that may be applicable to disaster situations. Emergency care providers must begin to plan effectively to utilize disaster-specific telemedicine applications to improve future outcomes.